PENGARUH PEMBERIAN PUPUK KOMPOS TERHADAP PERTUMBUHAN TANAMAN SAWI HIJAU (Brassica juncea L.) - Arum Mega Digdayanti (Program Studi Pendidikan Biologi, 2021)
Abstract: The green mustard plant is an annual plant and has short stems. The green mustard plant is included in the Brassicaceae family whose leaves can be used for consumption. The purpose of this research is to determine the best compost dosage for growth a leaf blade length, leaf width and wet weight of green mustard plants. This type research is experiential quanti. The method used of this research is completely randomized design (CRD) with 5 treatments and 4 replications. The treatments in this study include A (control treatment), B (compost 550 gr), C (compost 650 gr), D (compost 750 gr), E (compost 850 gr). The research result of growth green mustard plants showed that the leaf blade length is obtained F count (30.36), leaf width obtained F count (5.64) and wet weight obtained F count (17.685) was greater than F table 5% ( 3.06) and 1% (4.89), then compost very significant effect of the growth greens green mustrad plant. The best dose of the growth green mustard plant is compost 850 gr to treatment E, so that can increase the growth green mustard plant this is leaf blade length, leaf width and wet weight.